Institutional Limits of Regional Counterterrorism: ECOWAS Responses to Boko Haram - Bah, Fatoumatta; Parasetyono, Edy (Universitas Tribhuwana Tunggadewi, 2025)
West Africa has witnessed a dramatic increase in terrorist violence in the last ten years, especially from Boko Haram-affiliated groups. There has been a corresponding rise in frequency and scale of attacks with thousands of civilian deaths, destruction of schools, health care facilities and market infrastructure, and mass displacement of populations throughout Nigeria, Niger, Cameroon and Chad. The geographical response has revolved mainly around the Economic Community of West African States (ECOWAS), which has come to adopt protocols and frameworks to prevent violent extremism and harmonize member states' responses against it. This paper assesses the level of effectiveness of ECOWAS in fighting terrorism, adopting a qualitative case study of Boko Haram. Based on ECOWAS communiqués, regional policy documents, and think tank reports from 2010 to 2024, the study uses process tracing to gauge how ECOWAS has responded to countering terrorist threats. The results indicate that even in the presence of formal mandates and regional commitments, ECOWAS struggles with substantial operational problems, such as financial constraints, limited power of enforcement, overlapping mandates with the African Union, and political unwillingness by member states. This study targets mechanisms for institutional response, thereby contributing to the existing literature on counterterrorism strategy by providing a locally grounded analysis of these strategies, which characterize regional security cooperation based on structural constraints and political dynamics.Afrika Barat telah menyaksikan peningkatan dramatis dalam kekerasan teroris selama sepuluh tahun terakhir, terutama dari kelompok-kelompok yang berafiliasi dengan Boko Haram. Peningkatan ini disertai dengan frekuensi dan skala serangan yang semakin besar, yang telah menyebabkan ribuan kematian warga sipil, penghancuran sekolah, fasilitas kesehatan, dan infrastruktur pasar, serta pengungsian massal penduduk di seluruh Nigeria, Niger, Kamerun, dan Chad. Respons secara geografis sebagian besar berpusat pada Komunitas Ekonomi Negara-Negara Afrika Barat (ECOWAS), yang telah mengadopsi protokol dan kerangka kerja untuk mencegah ekstremisme kekerasan serta menyelaraskan respons negara-negara anggotanya terhadap ancaman tersebut. Penelitian ini mengevaluasi tingkat efektivitas ECOWAS dalam memerangi terorisme, dengan menggunakan studi kasus kualitatif terhadap Boko Haram. Berdasarkan komunike ECOWAS, dokumen kebijakan regional, dan laporan lembaga pemikir dari tahun 2010 hingga 2024, studi ini menggunakan metode process tracing untuk menilai bagaimana ECOWAS merespons ancaman teroris. Hasil penelitian menunjukkan bahwa meskipun terdapat mandat formal dan komitmen regional, ECOWAS masih menghadapi berbagai permasalahan operasional yang signifikan, seperti keterbatasan keuangan.